Development and Evaluation of a No-Code-Based Cash Flow Information System Using Base44 for Financial Reporting Monitoring (Case Study: Zanjus) - Amalia Amalia; Fajar ‘Ainur Ridhwan; Salman Fathy Shiroth (Information Technology and Science (ITScience), 2026)
Digital transformation in the financial management of small and medium enterprises (SMEs) has become an essential requirement for improving the efficiency, transparency, and accuracy of financial reporting. However, most student-run businesses still record transactions manually using simple spreadsheets, which makes them prone to recording errors and delays in cash flow monitoring. This study aims to develop a Cash Flow Information System based on no-code using the Base44 platform to support financial reporting monitoring for the Zanjus student business. The study employed the Research and Development (R&D) method with the Waterfall development model, encompassing the stages of requirements analysis, design, implementation, testing, and evaluation. Data were collected through semi-structured interviews and documentation, while system testing was carried out using Black Box Testing and User Acceptance Testing (UAT). The results show that the system successfully integrates the recording of income and expense transactions, a real-time financial monitoring dashboard, and automated financial reporting in the form of a general journal, ledger, cash flow statement, income statement, and balance sheet. The results of the Black Box Testing indicate that all system features function in accordance with the functional requirements. Meanwhile, the UAT results, which involved five core participants (CEO, CFO, COO, CMO, and CCO), yielded an average score of 96.75%, placing the system in the “Very Good” category within the context of this single case study; the result therefore cannot yet be generalized to a broader user population. This study also produced user-needs-based design principles encompassing interface simplicity, real-time transparency, reporting automation, and development flexibility. The study contributes academically by advancing research on the implementation of no-code platforms in Accounting Information Systems, while also offering a practical contribution in the form of a digital solution that is easy to use for non-technical users within the student SME environment.